The root causes of ineffective and inefficient healthcare technology management in Benin public health sector - Houngbo, Pamphile Thierry; Zweekhorst, Marjolein; Bunders, Joske; Coleman, Harry Laurence Selby; MEDENOU, DATON; Dakpanon, Laurent; De Cock Buning, Tjard (My University, 2017)
This study aims to identify the root causes and solutions of main problems facing Healthcare Technology Management in Benin's public health sector. Conducted in Benin from 2008 to 2010, two surveys were used with key actors in Healthcare Technology Management. The ﬁrst survey was based on 377 questionnaires and 259 interviews, and the second involved observation and group interviews at selected health facilities The ﬁndings of the two surveys show that the problems are based on both high- and low-level corruption, characterized by self-interest and unwillingness of the policy makers to solve healthcare care equipment and maintenance problems. Appropriate solutions include: (i) development of policy and management tools to guide distribution, (ii) the use of reference price lists for procuring equipment, (iii) development of policy and management tools to guide ﬁnancial resource allocation on the life cycle cost of the equipment, (iv) creation of a healthcare equipment and maintenance directorate, (v) development of policy and management tools for obsolete equipment, and (iv) the development of a new healthcare technology management policy with a budgeted action plan. We suggest that much can be improved by the strict development and implementation of policy and management tools, as well as regulations at each level of the Healthcare Technology Management process. A key role has to be attributed to the technical specialists, and the end users of equipment in healthcare facilities. Furthermore, there is a need for capacity building in Healthcare Technology Management institutions.
Keywords: Healthcare technology management; Policy and management; tools; Root cause analysis; Corruption